Microwave ablation vs. liver resection for patients with hepatocellular carcinomas - Hyundam Gu; Yeonjoo Seo; Dong Jin Chung; Kwang Yeol Paik; Seung Kew Yoon; Jihye Lim (Journal of Liver Cancer)
Backgrounds/Aims Microwave ablation (MWA) is an emerging ablative therapy that surpasses previous methods by achieving higher temperatures and creating larger ablation zones within shorter periods. This study compared the therapeutic outcomes of MWA with those of liver resection in real-world clinical practice. Methods A total of 178 patients with 259 nodules who underwent MWA or liver resection between January 2015 and July 2023 were enrolled. Local tumor progression (LTP)-free survival, overall progression (OP)-free survival, and overall survival (OS) were assessed based on the treatment modality for the index nodule. Results Of the 178 patients, 134 with 214 nodules underwent MWA, and 44 with 45 nodules underwent liver resection. The median follow-up period was 2.0±1.5 years. The annual incidence of LTP was 3.7% for MWA and 1.4% for liver resection. Treatment modality did not significantly affect LTP-free survival (hazard ratio, 0.61; 95% confidence interval, 0.14-2.69; P=0.511). For nodules larger than 3 cm, LTP-free survival was not affected by the treatment modality. Similarly, OP-free survival and OS were not influenced by treatment modality. Conclusions MWA and liver resection demonstrated comparable treatment outcomes in terms of local tumor control, overall recurrence, and survival. MWA may be an alternative treatment option for select patients; however, further studies are necessary to generalize these findings.